Quantificação da microbiota do solo em diferentes sistemas de manejo com uso de vinhaça e queima em cana-de-açúcar, na Bacia Tenente Amaral-Jaciara-MT - Palú, Andréa Aquino de Assis (2013)
This study aimed to analyze the microbial community and to characterize it as the phenotypically and quantitatively different management systems, the following treatment areas: sandy (with and without vinasse), clayey (with and without vinasse), sandy loam (with burning) and cerrado sensu stricto. Microbiological analyzes were used, as well as the physical -chemical soil efflux of CO2 and total organic carbon. From the results, it was observed that the quantification of bacteria and fungi did not differ statistically in any of the areas, however it was found that the predominant bacteria in the sandy area and cerrado at a depth of 0-5 cm. To quantify fungi was greater in sandy area without vinasse in the 0-5 cm depth. The analysis morfotintorial Gram allowed the separation of two groups, Gram positive and negative bacteria as well as the shapes and coco rods. It was found that most are Gram positive, with 80 % Gram negative 8%, followed by gram-positive cocci and 10% Gram negative 2%. In relation to phenotypic characteristics were identified 61 known genus, the genus Bacillus sp which had the highest amount. To correlate the physical and chemical attributes soil with microorganisms was significant variables: temperature, pH, TOC, calcium, magnesium and potassium in the depths 0-5 cm, 5-10 cm and 10-20 cm. The CO2 efflux correlated with the attributes TOC, temperature, pH and humidity. In this study it is concluded that the growth of bacteria and fungi was prevalent in depth surface analysis with respect to morphology Gram dyeing was a higher incidence of positive rods group, the majority of the family Bacillaceae. The physical and chemical attributes have been studied, temperature, pH , TOC, calcium , magnesium and potassium were those which have had a greatest influence on microbial growth at depths 0-5 cm, 5-10 cm and 10- 20cm.